البنك الدولي و دوره في التنمية الدولية - غادة بوعلاق; مروة سيوان (My University, 2021)
Summary The World Bank is one of the specialized agencies of the United Nations dealing with development, the beating heart of the international financial system and one of the pillars of the international monetary system. It began its activity by helping to rebuild Europe after the Second World War, an idea that developed during the war in Bretton Woods in the United States state of New Hampshire in 1946. Reconstruction efforts continued to be an important focus of the World Bank's work in the light of natural disasters, humanitarian emergencies and post-conflict rehabilitation needs, which have always affected the economies of developing countries. The Bank's work is focused on poverty alleviation as a working objective and encompasses all its work. The number of World Bank member States is 189 and the World Bank is composed of a group of five global organizations responsible for financing countries for the development and promotion of global investment: the International Bank for Reconstruction and Development, the International Development Corporation, the International Finance Corporation, the International Investment Guarantee Agency and the International Centre for the Settlement of Investment Disputes. Over the years, the World Bank has played an important role in promoting investment and capital development for the reconstruction and development of member countries through the creation of large enterprises, the formulation of global policies and their development for the modernization of public and private sector management, as well as the promotion of FDI. The World Bank has concluded numerous agreements with a range of developing countries, including Jordan and the Sudan, to assist them in achieving development and eradicating poverty, providing them with a range of loans to encourage them to advance their agricultural, industrial and environmental sectors. The World Bank's vision and modus operandi have contributed significantly to defining its relationship with Algeria as one of the most prominent developing countries. The foundation of their strategic partnership framework has been the provision of reimbursable advisory services. In our view, the World Bank is one of the world's most important international financial institutions seeking to achieve development in various areas in order to realize its ambitious dream of a world free of poverty by 2030. ............... الملخص البنك الدولي هو أحد الوكالات المتخصصة في الأمم في المتحدة التي تعتني بالتنمية، والقلب النابض لرأس النظام المالي الدولي وأحد ركائز النظام النقدي الدولي، وقد بدأ نشاطه بالمساعدة في إعادة إعمار أوروبا بعد الحرب العالمية الثانية وهي الفكرة التي تبلورت خلال الحرب في "بريتون وودز في ولاية نيوهامشير الأمريكية سنة 1946 . واستمرت جهود الإعمار موضع تركيز هام لعمل البنك الدولي ذلك في ظل الكوارث الطبيعية و الطوارئ الإنسانية واحتياجات إعادة التأهيل في ما بعد النزاعات والتي دائما ما تؤثر على اقتصاديات البلدان النامية عمل البنك يتمركز حول تخفيف حدة الفقر كهدف عامل و يشمل جميع أعماله. ويبلغ عدد الدول الأعضاء في البنك الدولي 189 بلدا مساهمين فيه ويتكون البنك الدولي من مجموعة مؤلفة من خمس منظمات عالمية مسؤولة عن تمويل البلدان بغرض تطوير وتشجيع الاستثمار العالمي وهي البنك الدولي للإنشاء والتعمير والمؤسسة الدولية للتنمية، ومؤسسة التمويل الدولية والوكالة الدولية لضمان الاستثمار والمركز الدولي لتسوية منازعات الاستثمار. وقام البنك الدولي طوال سنوات بدور هام في تشجيع الاستثمار وتنمية رؤوس الأموال بغرض تعمير و تنمية البلدان الأعضاء عن طريق إنشاء مشروعات ضخمة، ورسم السياسات العالمية، وتطويرها من أجل تحديث إدارة القطاع العام والخاص، بالإضافة إلى تشجيع الاستثمار الأجنبي المباشر. وأبرم البنك الدولي العديد من الاتفاقيات مع مجموعة من الدول النامية، من بينها الأردن والسودان لمساعدتها على تحقيق التنمية والتخلص من براثن الفقر، فقدم إليها مجموعة من القروض لتشجيعها على النهوض بقطاعاتها الزراعية والصناعية والبيئية. وساهمت كثيرا نظرة البنك الدولي و طريقة عمله في تحديد معالم علاقته بالجزائر باعتبارها من أبرز الدول النامية، فكان ارتكاز إطار الشراكة الإستراتيجية بينهم هو تقديم الخدمات الاستشارية مستردة التكاليف. ومنه نرى أن البنك الدولي من أهم المؤسسات التمويلية الدولية في العالم يسعى إلى تحقيق تنمية في مختلف المجالات وذلك من أجل تحقيق حلمه الطموح وهو عالم خالي من الفقر بحلول عام 2030. .................... Résumé La Banque mondiale est l’une des institutions spécialisées des Nations Unies en matière de développement, le cœur battant du système financier international et l’un des piliers du système monétaire international. Il a commencé son activité en aidant à reconstruire l’Europe après la Seconde Guerre mondiale, une idée qui s’est développée pendant la guerre à Bretton Woods aux États-Unis du New Hampshire en 1946. Les efforts de reconstruction ont continué d’être un axe important du travail de la Banque mondiale à la lumière des catastrophes naturelles, des urgences humanitaires et des besoins de réhabilitation après un conflit, qui ont toujours affecté les économies des pays en développement. Le travail de la Banque est axé sur la réduction de la pauvreté en tant qu’objectif de travail et englobe tous ses travaux. Le nombre d’États membres de la Banque mondiale est de 189 et la Banque mondiale est composée d’un groupe de cinq organisations mondiales responsables du financement des pays pour le développement et la promotion de l’investissement mondial : la Banque internationale pour la reconstruction et le développement, la Société internationale de développement, la Société financière internationale, l’Agence internationale de garantie des investissements et le Centre international pour le règlement des différends relatifs aux investissements. Au fil des ans, la Banque mondiale a joué un rôle important dans la promotion de l’investissement et du développement du capital pour la reconstruction et le développement des pays membres par la création de grandes entreprises, la formulation de politiques globales et leur développement pour la modernisation de la gestion des secteurs public et privé, ainsi que la promotion des IDE. La Banque mondiale a conclu de nombreux accords avec un certain nombre de pays en développement, dont la Jordanie et le Soudan, pour les aider à atteindre le développement et à éradiquer la pauvreté, en leur accordant une série de prêts pour les encourager à promouvoir leur agriculture, secteurs industriels et environnementaux. La vision et le modus operandi de la Banque mondiale ont largement contribué à définir sa relation avec l’Algérie comme l’un des pays en développement les plus importants. Leur cadre de partenariat stratégique repose sur la prestation de services consultatifs remboursables. À notre avis, la Banque mondiale est l’une des institutions financières internationales les plus importantes du monde qui cherche à se développer dans divers domaines afin de réaliser son rêve ambitieux d’un monde libéré de la pauvreté d’ici 2030.